MANAGEMENT OF ORAL LEUKOPLAKIA - ANALYSIS OF THE LITERATURE - Elitsa G. Deliverska; Milena Petkova (Peytchinski Publishing, 2017)
Oral leukoplakia is the most common potentially malignant disorder affecting oral cavity. Various surgical and non-surgical treatments have been reported, but currently there is no universal consensus on the most appropriate one and on the duration or interval of follow-up of patients with this condition. The aim of this article is to present a review of the management of oral leukoplakia according to the literature until now. Management of oral leukoplakia should begin with elimination of risk factors (if any) such as tobacco abuse, betel chewing, alcohol abuse, superimposed candida infection over the lesion etc. Conservative treatment includes use of chemopreventive agents such as vitamins (vitamins A, C, E), fenretinide (Vitamin A analogue), carotenoids (beta-carotene, lycopene), bleomycin, protease inhibitor, anti-inflammatory drugs, green tea, curcuma etc. Surgical treatment includes conventional surgery, electrocoagulation, cryosurgery, and laser surgery (excision or evaporation). The main purpose of oral leukoplakia management is to avoid malignant transformation of the lesion or if this happened to detect this in early stages.